Formation of the fairy tale matrix of a dragon slayer - Tratnik, Polona (Acta Histriae, 2022)
In the article the author examines how the matrix of the dragon killer appeared in different social contexts and its formation as a fairy tale matrix. She traces the genealogy of the dragon slayer matrix back to ancient mythologies, paying regard to Babylonian, Greek, Celtic, and Slavic mythologies, as well as to the Christian codes and appearances in (particularly Slovenian) folklore, and discusses the variations that occur with different uses of the matrix, in different historical moments and epistemes. Special attention is devoted to studying the social and political functions the tales about the dragon killer had in the contexts in which they appeared.
Keywords: desetina; Kresnik; ljudske pravljice; miti; pravljice; slovanska mitologija; sveti Jurij; Zeleni Jurij; zmaji